Avaliação soroepidemiológica de Toxoplasma gondii em humanos e sua relação com o convívio com gatos (Felis catus) como animal de estimação - Santos, Luciana Siqueira Silveira dos (2012)
Toxoplasma gondii is causative agent of a protozoonosis of public health importance, toxoplasmosis, that may have serious consequences on species infected. Cats are definitive hosts of the protozoan, when they become infected they eliminate oocysts and may become a source of infection for humans. There are controversies in the results of different authors about living with pet cats as a risk factor for human infection. This study analyzed serum samples from 108 individuals who have or had cats and from 110 individuals who do not like cats and never had one. An epidemiological questionnaire was applied. The results indicated seroprevalence of 39.8% for the individuals who live with cats and 26.4% for the 110 individuals who never had these animals. The analysis of risk factors showed significant association between seropositivity and of variables: aged over 31 years (p = 0.0000), living with cats (p = 0.0143) and handling of raw meat (p = 0.0290). It was concluded that even in a population with a high level of education, living with cats may increase twice the chance of infection by T. gondii, when the animals are not kept in the household and in adequate sanitary conditions.